Modelling complex networks by random hierarchical graphs - Wróbel, M. (Condensed Matter Physics, 2008)
Numerous complex networks contain special patterns, called network motifs. These are specific subgraphs,
which occur oftener than in randomized networks of Erd˝os-R´enyi type. We choose one of them, the triangle,
and build a family of random hierarchical graphs, being Sierpi ´nski gasket-based graphs with random “decorations”.
We calculate the important characteristics of these graphs – average degree, average shortest path
length, small-world graph family characteristics. They depend on probability of decorations. We analyze the
Ising model on our graphs and describe its critical properties using a renormalization-group technique. Багато комплексних мереж мiстять особливi шаблони, так званi мережевi мотиви. Вони є спецiальними пiдграфами, що з’являються частiше нiж у випадкових мережах типу Ердоша-Ренi. Ми обрали один з таких шаблонiв – трикутник, i побудували сiмейство випадкових iєрархiчних графiв, визначених за гаскетом Серпiнського з випадковими “декорацiями”. Розрахованi важливi характеристики таких графiв – середнiй ступiнь, середня довжина шляху, характеристики сiмейства графiв “тiсного свiту”. Вони залежать вiд iмовiрностi декорацiй. Проаналiзовано модель Iзiнга на наших графах, описано її критичнi властивостi з використанням методу ренорм-групи.